Augmented Virtuality Systems as a Tool for Improving Numeracy Decision-Making Among Children. (August 2022) - Yuviler-Gavish, N; Treiger, Z; Horesh, E; Shamilov, E
Young children depend on the non-symbolic representation of numbers for their numeracy understanding and decision-making. The objective of the current research was to examine whether the use of an augmented virtuality (AV) system to represent numbers as physical objects, compared to representing them only visually on a computer screen, will improve children's numeracy decision-making. The question was evaluated by comparing children's decisions to buy more profitable versus non-profitable products, as well as their total profit, when the coins and the coin machine are real (AV system group) compared to their decisions when using a system in which the coins and the coin machine are virtual (virtual system group). Two between-participants groups of children aged 6–8 participated in this study, with 30 children in each group. The results demonstrated that in the AV system group, the children invested more proportionately in the profitable versus non-profitable products, while in the virtual system group, the opposite occurred. As a result of their better decision-making, the total profits of the AV system group were higher than those of the virtual system group. The current findings are an interesting addition to the existing literature on the contribution of virtual reality and augmented reality systems in improving mathematical learning.